Pengembangan Digitalisasi UMKM Kerajinan Kelurahan Sentul Untuk Perluasan Pemasaran - Nadhifatul Azizah Putri Bachtiar; Kustini Kustini; Ruthyanti Manihuruk; Sukma Alexander Putri (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Micro, Small and Medium Enterprises (MSMEs) which are active in the world of handicrafts in the Sentul Village area are one of the community service partners. Through changes in the 4.0 revolution which is accompanied by changes in digitalization through the development of technology and information. Adaptation of changes to MSMEs is also needed in the modernization of digitalization by implementing various innovations. The existence of innovation from various technologies and information is what helps MSMEs to keep moving in increasing consumers, namely with digital marketing. The method used in community service activities in the Sentul sub-district is a qualitative approach as well as the socialization and implementation of MSMEs assistance. The results of this activity are services in creating business accounts on digital media such as Instagram, Tiktok, shopee accounts, with optimal management of digital media, as well as making product photos.